Numerical study of electromagnetic field intensity in a partially shielded inhomogeneous half ball - O.S. Skvortsov; A.A. Tsupak (Известия высших учебных заведений. Поволжский регион: Физико-математические науки)
Background. The purpose of the work is to develop, implement and test a projection method for comparing methods of focusing electromagnetic fields passing through a dielectric partially shielded half ball. Material and methods. The Galerkin method is implemented for the vector integro-differential equation of the diffraction problem; basic vector functions in a three-dimensional solid and a parameterized nonplanar screen are determined; a parallel algorithm for solving the problem using the MSMPI library is implemented. Results. Various options for shielding the half ball in order to focus the electric field inside the body were compared. Conclusions: the most effective method of focusing the wave in the proposed arrangement of the screen-body system has been selected.